THE EFFECTIVENESS OF FIXED ASSET MANAGEMENT IN SUPPORTING ORGANIZATIONAL PERFORMANCE: EVIDENCE FROM THE REGIONAL SECRETARIAT OF KENDARI CITY - Muh. Rijal; Muhammad Yusuf; Sarinah (INTERNATIONAL JOURNAL OF FINANCIAL ECONOMICS, 2026)
This study aims to analyze the effectiveness of fixed asset management in supporting organizational performance at the Regional Secretariat of Kendari City. The study employed a qualitative approach using a descriptive method. Data were collected through observation, interviews, and documentation studies involving informants selected through purposive sampling, namely the Asset Manager of the Regional Secretariat of Kendari City and staff responsible for regional asset management. Data analysis was conducted through the stages of data collection, data reduction, data display, and conclusion drawing. The results indicate that fixed asset management at the Regional Secretariat of Kendari City has been implemented through eight stages: asset needs planning, asset procurement, asset inventory, asset legal audit, asset valuation, asset maintenance, asset disposal, and asset transfer. Overall, the implementation of fixed asset management has been carried out effectively and in accordance with applicable regulations and procedures, referring to the asset management theory proposed by Gima A. Sugiama. The effectiveness of fixed asset management is reflected in the availability of facilities and infrastructure that support the implementation of organizational duties and functions, the optimal maintenance of assets, and the improvement of efficiency and smoothness in organizational operations. However, several challenges remain, particularly in asset data management and the updating of asset information, which require further attention to enhance the quality of asset management in the future.